Family support, the role of cadres and the activeness of the elderly in participating in posyandu in Pattan Ulusalu Village, Saluputti District, Tana Toraja Regency - Hayuti Windah Pagiu; Bahtiar Bahtiar; Sriwinda Lediana Barung; Heni Riana Nada (Alliance oh Health Activists (AloHA), 2025)
Family support is a person's attitude towards family members in the form of emotional support, while the role of a cadre is someone whose duty is to volunteer to help and ensure the smooth implementation of the integrated elderly service post. This research aimed to analyze the relationship between family support and the role of cadres and the activeness of elderly people in participating in integrated elderly service posts. This research implemented a cross-sectional design, involving 46 respondents selected in Pattan Ulusalu Village, Tana Toraja. Data about family support, the role of cadres and the activeness of the elderly were measured through filling out questionnaires. Data were analyzed descriptively and continued with the Chi-square test. The analysis result for the first objective was p value = 0.338, while for the second objective, p value = 0.249. It was concluded that there was no correlation between cadre support and the role of cadres and the activeness of the elderly in the integrated elderly service center. Keywords: elderly; integrated service center; family support; the role of cadres; elderly activeness